Gambaran Penyakit Hiperkolesterol dan Febris terhadap Jenis Kelamin di Puskesmas Watunohu - Bulan, Sahari; Lestari, Catur Retno (Indonesian Journal of Biomedical Science and Health; Vol 1 No 1 (2021): Agustus 2021DO - 10.31331/ijbsh.v1i1.1839, 2021)
The increase number of patient were caused by any diseases as the effects of unhealthy lifestyle. One of these diseases is hypercholesterolemia and fibers. Cholesterol is a natural substance which has steroid formula but it characterized as fats. It is also good essential for another substances and insulating material around fibers. But, the cholesterol must be balanced in consuming it, because it can be caused death if people over-consumed the cholesterol. This study is a cross-sectional study with quantitative approach by using primarily data. The data was collected from total of patients in Puskesmas Watunoho during 5 months, that was begin from January until June 2021 in aimed to know the number of hypercholesterolemia and fibers patients. The variable of this study is gender with the total number of hypercholesterolemia patients as much as 118 people and the total number of fibers patients as much as 430 people. The result of this study is the average of women who had cholesterol disease are 11 and the average of men who had cholesterol disease are 8.67. Then, the average of women who had fibers disease are 34.8 and the average of men who had fibers are 33.5. It can be concluded that there is no significant between hypercholesterolemia and fibers between genders of patients.